2005
DOI: 10.1213/01.ane.0000166763.24782.26
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Produced by Pseudomonas Bacteremia Does Not Alter Plasma Volume Expansion After 0.9% Saline Infusion in Sheep

Abstract: Clinicians generally consider sepsis to be a state in which fluid is poorly retained within the vasculature and accumulates within the interstitium. We hypothesized that infusion of 0.9% saline in conscious, chronically instrumented sheep with hyperdynamic bacteremic sepsis would be associated with less plasma volume expansion (PVE) and greater interstitial fluid volume expansion than in conscious, nonseptic sheep. Six conscious adult sheep received an IV infusion of 25 mL/kg of 0.9% saline over 20 min (1.25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…It appears that small molecular fluids in this setting shift in a more physiologic way unaffected by the protein level. Likewise, in a sheep study during early and late sepsis over a 3-hr interval, there were no differences in distribution or elimination of infused crystalloids found neither by mass balance analysis nor volume kinetic analysis (16).…”
Section: Discussionmentioning
confidence: 84%
“…It appears that small molecular fluids in this setting shift in a more physiologic way unaffected by the protein level. Likewise, in a sheep study during early and late sepsis over a 3-hr interval, there were no differences in distribution or elimination of infused crystalloids found neither by mass balance analysis nor volume kinetic analysis (16).…”
Section: Discussionmentioning
confidence: 84%
“…Chappell et al further summarize that the endothelial glycocalyx can bind free plasma and they form together the endothelial surface layer and that an oncotic gradient seems to be present directly across the endothelial surface layer, that defines finally vascular integrity, so that the presence of this layer should be the basic requirement for a physiologic barrier function (21). Additionally Svensen et al, (22) showed that in septic and burn-injured sheep that the intravascular retention of infused fluid is paradoxically maintained despite increased microvascular protein permeability and a reduced plasma-to-tissue oncotic gradient (22). Thus, isotonic crystalloid components due to their small size can leak regardless of the state of the endothelial barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In a cat model of trauma with capillary leakage, dextran or albumin induced greater volume expansion than did HES 130/0.4 or saline, and no differences were noted between HES 130/0.4 and saline over a 3‐h period (12). In a sheep model, plasma volume expansion in response to 0.9% saline was similar in animals with and without sepsis (26). Our study suggests that HES 130/0.4 may remain within the intravascular space even in patients with capillary leak syndrome.…”
Section: Discussionmentioning
confidence: 99%